Chemical communication connects soil food webs. (November 2016) - DeAngelis, Kristen M.
Abstract: Food webs are conceptual maps of ecosystem matter and energy flows, intended to illustrate the connections between organisms at different trophic and phylogenetic levels. All organisms communicate, most by way of diffusion of chemical signals, often in a density-dependent manner. In this essay, I suggest that food web interactions are regulated by extracellular, inter-species and often inter-domain communication. Defining the web of chemical communication in soils may illuminate new food web interactions and improve our understanding for how disturbances will reverberate through trophic interactions in terrestrial ecosystems. Highlights: Matter and energy flows are regulated by extracellular communication. Communication can occur within and across species and domains of life. Mapping chemical signaling onto soil food webs illustrates biotic interactions. A systems biology approach is needed to predict food web interactions by signals.